Examining the Relationship between Socialization Tactics and OCB: Mediating Role of OC (Global Journal of Management and Business Research, 2014)
Organizational citizenship behavior has always been of paramount importance for organizations to work at their best and despite the huge amount of research on it little is known of the processes that can ensure the salvation of such behavior. The present study has laid down a blueprint of how the implicit processes affect OCBs. In this study we have proposed a complete process by which extra-role behaviors can be ensured by the use of socialization tactics regardless of personality traits of the employees. Furthermore, organizational commitment has been proposed to act as a lubricant between socialization tactics and OCB. The implications for future research are proposed for an empirical evidence of the conceptual model proposed after a critical analysis of literature.
Keywords: socialization; organizational commitment; Furthermore